Lipoprotein (a) polymorphism as a risk factor of coronary and carotid atherosclerosis and its complications in women - O. I. Afanasyeva; M. V. Ezhov; M. S. Safarova; M. I. Afanasyeva; I. Yu. Adamova; S. N. Pokrovsky (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To investigate the role of lipoprotein(a) (Lp(a)) and apoprotein (a) (apo(a)) phenotype in pathogenesis of coronary artery (CorA) and carotid artery (CarA) atherosclerosis and its complications in women. Material and methods. The study included 200 women aged 55±10 years. All participants were divided into two groups, with (n=165) or without (n=35) diagnosed CorA and CarA atherosclerosis. In all patients, lipid profile parameters, Lp(a), and apo(a) phenotype were assessed. Results. Patients with atherosclerosis, compared to the controls, demonstrated higher prevalence of Lp(a) concentration ≥30 mg/dl (41,5% and 22,8%, respectively), low-molecular phenotype (LMP) of apo(a) (36,6% and 11,4%), and their combination (28,5% and 8,7%). Lp(a) concentration and LMP apo(a) prevalence were positively associated with the number of atherosclerotic CorA. Severe CorA atherosclerosis was 10 times more prevalent in women with LMP apo(a) and Lp(a) level ≥30 mg/dl than in women without LMP apo(a) and normal Lp(a) concentration. The combination of LMP apo(a) and Lp(a) ≥30 mg/dl significantly correlated with myocardial infarction in anamnesis, after adjustment for smoking status and lipid profile parameters (r=0,386, р<0,005). Increased intima-media thickness was stronger associated with LMP apo(a) than increased Lp(a) concentration. CarA atherosclerosis was 4 times more prevalent in patients with LMP apo(a) than in individuals with high-molecular apo(a) phenotype, and 5 times more prevalent in patients with the combination of LMP apo(a) and increased Lp(a) concentration than in subjects with high-molecular apo(a) phenotype and normal Lp(a) levels. Conclusion. Increased Lp(a) concentration, LMP apo(a), and their combination were independently associated with the presence and severity of CorA and CarA atherosclerosis in women.